Comparison of knowledge to antimicrobial stewardship institution policies targeting Staphylococcus aureus bacteremia and candidemia between medical doctors and pharmacists in an academic teaching hospital in Japan. Issue 5 (May 2019) - Moriyama, Yuki; Ishikane, Masahiro; Hayakawa, Kayoko; Yamamoto, Kei; Akazawa, Tsubasa; Sugiki, Yuko; Ohmagari, Norio
Abstract: Staphylococcus aureus bacteremia (SAB) and candidemia have significant impacts on mortality. Both have important implications for antimicrobial stewardship programs (ASPs). However, there are limited data regarding who should be educated and what components should be considered for the ASPs. Hence, we investigated the possibility of the key elements for implications of SAB and candidemia managements for ASPs. We conducted a cross-sectional study on the knowledge of antimicrobial stewardship institution policies targeting SAB and candidemia for all medical doctors (MDs) and pharmacists to using an E-learning system. To compare the differences in proportions of appropriate knowledge between junior residents and other MDs, and all MDs and pharmacists, we performed bivariate analyses using Fisher's exact test and χ 2 test with odds ratios (ORs) with 95% confidence intervals (CIs). In total, all 395 MDs (71 junior residents, 137 senior residents and fellows, and 187 attending doctors) and all 63 pharmacists including 4 antimicrobial stewardship teams pharmacists responded to survey. MDs other than junior residents responded significantly inappropriately to the questions on the candidemia than junior residents (OR = 0.6, 95% CI: 0.4–1.0). Pharmacists had a significantly lower proportion of appropriate knowledge to the candidemia than MDs (OR = 0.4, 95% CI: 0.2–0.8). The major pitfall was failure to consult an ophthalmologist (82.5%). Next step, we will conduct educational intervention about institution policies, and evaluate whether to improve the knowledges and practices by pre-post test and chart review.